A lei e a ética na administração de empresas privadas: estudo exploratório regional - Ghisi, Marina Litzinger (2008)
Exploratory study relating law and business ethics, through the analysis of three Brazilian Laws: Consumer s Defense Code, Work Convention Agreement 2007/2008 between tourism companies syndicate and employees syndicate valid in the city of Foz do Iguaçu and Environmental Crimes Law, as well as through the opinion of clients and suppliers about the first, of employers and employees about the second and of the community and managers about the third. The results showed that the Brazilian Law cannot be seen as a whole or as a sole concept: for each law has unique characteristics at least concerning business activities. As a theoretical reference for ethics, Habermas s ideas were used, although it was not a good choice to study the Environmental Law. The research indicated that the Consumer s Code and the Work Convention seem to induce cooperation and ethics in the relationships between private companies and clients and private companies and employees. It also indicated the need of deeper studies about business laws and business ethics, because the laws obligate the companies and disregarding them may lead to failure, and ethics represents the best of humanity, and should not be excluded or ignored in the researches or teaching of business.